2023
DOI: 10.3389/fonc.2023.938042
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer subtype and clinical characteristics in women from Peru

Abstract: IntroductionBreast cancer is a heterogeneous disease, and the distribution of the different subtypes varies by race/ethnic category in the United States and by country. Established breast cancer-associated factors impact subtype-specific risk; however, these included limited or no representation of Latin American diversity. To address this gap in knowledge, we report a description of demographic, reproductive, and lifestyle breast cancer-associated factors by age at diagnosis and disease subtype for The Peruvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 110 publications
(109 reference statements)
1
4
0
2
Order By: Relevance
“…Finally, the number of articles was reduced to 26, which will be used to develop the systematic literature review. From the different databases, eight articles published during the year 2023 were identified [1], [3], [4], [6], [11], [13], [14], along with eight articles from the year 2022 [2], [5], [7][8][9][10], [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], all of which met the filters established in the methodology, and that is why they were selected. The will above aids in conducting the review with data from up-to-date research grounded in knowledge from subsequent years.…”
Section: Jimenez Ayalamentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the number of articles was reduced to 26, which will be used to develop the systematic literature review. From the different databases, eight articles published during the year 2023 were identified [1], [3], [4], [6], [11], [13], [14], along with eight articles from the year 2022 [2], [5], [7][8][9][10], [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], all of which met the filters established in the methodology, and that is why they were selected. The will above aids in conducting the review with data from up-to-date research grounded in knowledge from subsequent years.…”
Section: Jimenez Ayalamentioning
confidence: 99%
“…Another limitation of ML, according to studies [2], [7], [9], [11], [13], [14], [21][22][23][24][25][26][27][28][29], is related to data. When the amount of data increases for ML-based systems, it becomes evident that the algorithm faces issues that prevent it from functioning correctly [1]; the performance of ML-based algorithms is considered conventional [9].…”
Section: Fig 6 Disadvantages Based On References In Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Oncologic anthropology is also relevant in studying the breast cancer burden of Latina/Hispanic women internationally. [27][28][29][30][31][32][33][34][35][36][37][38][39][40] Ancestry-associated variants have been identified that predict risk from specific breast cancer phenotypes among Latina women in the United States, in Central America, and in South America. These studies have also found that among admixed Latina women, the extent of European ancestry increases the risk of breast cancer, whereas extent of Indigenous American ancestry decreases the risk of breast cancer.…”
Section: Oncologic Anthropology: Influence Of Germline Genetic Ancest...mentioning
confidence: 99%
“…Oncologic anthropology is also relevant in studying the breast cancer burden of Latina/Hispanic women internationally 27–40 . Ancestry‐associated variants have been identified that predict risk from specific breast cancer phenotypes among Latina women in the United States, in Central America, and in South America.…”
Section: Oncologic Anthropology: Influence Of Germline Genetic Ancest...mentioning
confidence: 99%